CONSTRUCTIVISM FROM PHILOSOPHY TO MATHEMATICS LEARNING - Jaka Wijaya Kusuma; Rochmad Rochmad; Isnarto Isnarto; Hamidah Hamidah (Yayasan Education and Social Center, 2021)
Constructivism, especially philosophy, understands that knowledge is the result of construction in a personal human being. Develop knowledge through social interaction with other human beings, phenomena, experiences, and environments. Knowledge is considered correct if it has significance for troubleshooting. Learning in a constructionist view offers to develop concepts and perceptions of the student itself. In the classroom process, teachers take on the role of moderators and facilitators. A constructivist teacher must understand the characteristics of a student's mistakes because the increase in knowledge is through mistakes and mistakes. Teachers should see mistakes as a source of information about the student's scheme of characteristics and thinking. There are four principles of constructivism in mathematical learning. First,the psychological structure must be before the occupation of the amount. Second, the structure of background knowledge (schemata) must be developed before teaching formal mathematics symbols. Third, students should have the opportunity to find and form their mathematical relationships, not to expose adult thinking. Fourth,teachers should create an atmosphere of thinking in the classroom